Cardiopulmonary exercise test as a diagnostic tool in chronic diseases in children and adolescents - Stasiak, Aleksandra; Kędziora, Piotr; Stańczyk, Jerzy (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Exercise testing is a diagnostic tool, which is permanently used in the diagnostic process of children with cardiovascular diseases. The ergospirometric test, otherwise known as the cardiopulmonary exercise test, is a widely used, non-invasive method of assessing the cardiovascular and respiratory response to exercise, both in adults and in children. The usual exercise test broadened with the analysis of the concentration of oxygen and carbon dioxide in exhaled air allows a more precise diagnosis of exercise intolerance, provides a possibility of differentiating the aetiology of this condition, and allows the assessment of the applied treatment method. Paediatric standards for ergospirometry have not been determined yet. In Poland, the ergospirometric test is still an underestimated tool for assessing physical performance and the impact of various childhood diseases on the cardiovascular and respiratory systems.